Upaya Gereja Mewujudkan Dialog Antar Umat Beragama dalam Konteks Kemajemukan Agama - Pribadyo Prakosa (Danum Pambelum: Jurnal Teologi dan Musik Gereja, 2023)
On the one hand, religious pluralism is something that can enrich the life of the Indonesian nation, but on the other hand it can become fertile ground for disputes, divisions, even bloodshed between one religion and another as well as acts of conflict and terrorism in the name of religion. Therefore, to avoid the outbreak of conflict between religious communities which could lead to violence, every religious follower needs to make efforts for dialogue between religious communities. The aim of the research is to describe and analyze the form and process of dialogue between religious communities carried out by the church, namely the Kalimantan Evangelical Church (GKE) Sion Basarang, Kapuas Regency, Central Kalimantan Province (hereinafter referred to as GKE Sion Basarang) which is one of the churches that lives in a pluralistic society both in terms of religion and ethnicity. The method used is qualitative with a descriptive-analytic research approach. The research results show that the form of dialogue between religious communities at GKE Sion Basarang is work dialogue and theological dialogue, meanwhile there are two stages in the dialogue process between religious communities, namely the first stage takes place spontaneously because church members live side by side in a pluralistic society and the The second is systematic because it is carried out through meetings between religious leaders, namely priests and other religious leaders.